Valuable voices; Invaluable Teaching/Learning Experiences - Bolt, Susan; Dickie, Laurence (Informing Science Press, 2010)
Providing excellent learning experiences for university students often depends on the ability of educators to understand students' learning needs. Formal and informal data collection tools are used to capture the students' voice which must be heard, understood and responded to appropriately by academic staff. At Curtin University in Western Australia the methods of enabling student experience to be voiced have developed over the last decade. Previously, manual data collection methods such as the Student Evaluation of Educational Quality (SEEQ) and the Unit Evaluation Questionnaire (UEQ) were used. However, since 2006 an online tool, eVALUate, has been used each semester to collect this data across the university.Despite the eVALUate tool being developed through consultative processes within the university, some academics have criticised its use because of low return rates, issues of interpretation about some questions and the diversity of contexts to which the same questions are applied. Although staff members are provided with reports quickly because of the electronic system, the data is collected at the end of semester and reports to academics are provided after students have left the units. Thus, as a summative report, academics are not able to respond directly to the students providing the feedback.Moreover, each of the seven sub-schools at Curtin Business School (CBS) determines its own methods for obtaining interim feedback from students in order to improve teaching/ learning processes and individual academics react differently to available formative feedback. In 2009, a faculty-wide, CBS survey was conducted to identify methods that were used to encourage students to give voice to their experience and describe the associated costs/ benefits of the usage of the devices. Data were collected by approaching the teaching & learning representatives of the seven sub-schools and asking them to respond to the questions in collaboration with their School colleagues.Their responses were collated and analysed by the Coordinator of Teaching & Learning and the results of the survey were reported back to Schools through the CBS Teaching & Learning Committee representatives. The current paper is used to review some of the literature in relation to giving voiceto the student experience, particularly related to the way in which it has been achieved at Curtin University. A description of the research methodology and the results of the CBS staff survey are discussed. It was apparent that a multiplicity of methods was used to give voice to the student experience. This multi-method approach is appropriate given the diverse nature of the student population at Universities and is offered as a contribution to the critical approach to the theme of student voice in this conference.